A New Approach for Solving Inverse Scattering Problems with Overset Grid Generation Method - Azarina Azman; Shafrida Sahrani; Kismet Hong Ping; Dayang Azra Awang Mat (Universitas Ahmad Dahlan, 2017)
This paper presents a new approach of Forward-Backward Time-Stepping (FBTS) utilizing Finite-Difference Time-Domain (FDTD) method with Overset Grid Generation (OGG) method to solve the inverse scattering problems for electromagnetic (EM) waves. The proposed FDTD method is combined with OGG method to reduce the geometrically complex problem to a simple set of grids. The grids can be modified easily without the need to regenerate the grid system, thus, it provide an efficient approach to integrate with the FBTS technique. Here, the characteristics of the EM waves are analyzed. For the research mentioned in this paper, the ‘measured’ signals are syntactic data generated by FDTD simulations. While the ‘simulated’ signals are the calculated data. The accuracy of the proposed approach is validated. Good agreements are obtained between simulation data and measured data. The proposed approach has the potential to provide useful quantitative information of the unknown object particularly for shape reconstruction, object detection and others.